Protection of Tree Functions Along Roads in Sidoarjo: Pelindungan Fungsi Pohon di Sepanjang Jalan di Sidoarjo - Prasetyo, Andika Bujang; Phahlevy, Rifqi Ridlo (Indonesian Journal of Law and Economics Review, 2025)
General Background: Trees play a vital role in maintaining environmental balance, particularly along roadways, contributing to ecological stability and human well-being. Specific Background: In Sidoarjo, tree protection policies are implemented by the Environmental Service to regulate business activities, yet challenges remain in enforcement. Knowledge Gap: Despite existing regulations, including Regent Regulation No. 29 of 2018, the protection of tree functions has not been fully effective, highlighting gaps between national law, local regulations, and practical implementation. Aims: This study aims to examine the legal protection of tree functions in Sidoarjo and assess regulatory implementation. Results: Findings indicate that while national and local regulations, such as UU No. 32/2009 and Perda No. 8/2013, provide a legal basis, the execution of tree protection policies remains suboptimal due to overly comprehensive local regulations that dilute enforcement strength. Novelty: The study integrates normative juridical analysis with local policy evaluation, providing a critical perspective on the alignment of environmental protection laws with administrative practice. Implications: Strengthening regulatory coherence and enforcement mechanisms is essential to ensure sustainable urban environmental management and fulfillment of citizens’ rights to a healthy environment. Highlights: National and local laws provide a strong legal basis for tree protection. Enforcement of tree protection in Sidoarjo is not yet optimal. Overly comprehensive local regulations reduce practical enforcement strength. Keywords: Tree Protection, Environmental Functions, Sidoarjo, Legal Regulation, Roadways